Comparative analysis of some legal terms in the civil legislation of the Republic of Kazakhstan and the Republic of Uzbekistan - Assetova, G.B.; Akimzhanova, M.T. (Bulletin of the Karaganda University “Law Series”, 2022)
The article presents a comparative legal analysis of the features of the use of some legal terms in the civil legal regulations of the Republic of Kazakhstan and the Republic of Uzbekistan. Regarding the relevance of the studied issue, the authors conclude that the ordering of legal terminology, as well as the resolution of its functional problems, is impossible without a deep scientific development of legal concepts, their logical analysis, and the establishment of an accurate definition. There is no consistent, improved terminology without clear, distinct legal concepts’ definitions. The authors of the article identify certain patterns in thedevelopment of legal terminology in civil law norms and acts. This can become the basis for the formation of a holistic picture of the creation of a legal language in the process of formation of the domestic civil law of the Republic of Kazakhstan. The purpose of this paper is to study the experience of the normative activity of the Republic of Uzbekistan and to develop recommendations aimed at improving the quality of legislation in the Republic of Kazakhstan. In conclusion, the authors emphasize the need for terminological unification of categories, concepts, and terms in law. This, in their opinion, will lead to certainty and clarity in the presentation of normative material and will not distort the meaning that is laid down in the legal norm by the legislator. During this study, the authors used such general methods of scientific cognition as synthesis, analysis, induction, deduction and comparative-legal, systemic, logical methods.